Pengaruh Pupuk Cair dari Limbah Kulit Semangka pada Pertumbuhan Selada Keriting - Hia, Indah Kurniati; Rahmiati, Rahmiati; Susilo, Ferdinand; Lubis, Rosliana (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2023)
Liquid organic fertilizer (LOF) is utilized as an alternative to enhance soil quality and crop yields. Organic waste from watermelon rinds (Citrullus lanatus) serves as one of the raw materials for LOF production. This study aims to assess the impact of LOF on the growth of curly lettuce (Lactuca sativa). The research employed an experimental method with five different LOF concentrations, ranging from no LOF (control) to 10% LOF. The results indicate that LOF application does not significantly affect the height of the plants, leaf count, leaf width, or the wet weight of curly lettuce. However, the use of undiluted 100 ml LOF leads to wilting and plant death, while increasing LOF concentration does not support the optimal growth of curly lettuce.